FOTO CERITA KEHIDUPAN KELOMPOK TANI KAMPUNG SUSUN BAYAM DALAM MENGHADAPI KRISIS AIR DAN LISTRIK USAI PEMBANGUNAN JAKARTA INTERNATIONAL STADIUM: LIFE PHOTO STORY OF KAMPUNG SUSUN BAYAM FARMER GROUP IN FACING THE WATER AND ELECTRICITY CRISIS AFTER THE JAKARTA INTERNATIONAL STADIUM CONSTRUCTION - Joseph; Silvia Amanda Aurelia Tahalea; Erlina Novianti (Fakultas Seni Rupa dan Desain, Universitas Trisakti, 2024)
Tani The Kampung Susun Bayam Farmers Group is a community dealing with housing rights issues, forcing them to live without essential services, such as water and electricity. This research aims to document their daily lives amid the water and electricity crisis that followed the construction of the Jakarta International Stadium. The method employed is qualitative with The study adopts a practice-based research approach, aiming to acquire new knowledge through direct practice. Writer using ohoto story style utilizing its nine elements to create a coherent narrative. Fifteen photo works were presented using the polyptychs technique, aligning photos in diptychs and triptychs. This research focuses specifically on the Kampung Susun Bayam residents facing the water and electricity crisis, but it can be expanded to explore their lives after relocation.